A retrospective study analysing outcomes of the coronectomy procedure at a university dental teaching clinic in Norway - Umar Sharif; Stein Atle Lie; Cecilie Gudveig Gjerde (Acta Odontologica Scandinavica)
Mandibular third molars (3M) are often associated with pathologies necessitating their surgical removal. Removal of 3M can cause injury to the inferior alveolar nerve (IAN). In coronectomy, a surgical option for 3M that present a significant risk of injury to the IAN, only the crown is removed, and the root/roots are left in situ, and may move after surgery.